Comprehensive Analysis of the Prognostic and Immunological Role of PAFAH1B in Pan-Cancer - Yuan, Yixiao; Jiang, Xiulin; Tang, Lin; Wang, Juan; Duan, Lincan (Frontiers in Molecular Biosciences, 2022)
Platelet-activating factor acetylhydrolase 1B3 (PAFAH1B3) plays a critical role in cancer initiation, metastasis, and progression; however, it remains unknown how PAFAH1B3 impacts cancer diagnosis and prognosis or regulates the immune response to different types of cancer. In this study, PAFAH1B3 was elevated in human pan-cancer, and this correlated with greater pathology and poor prognosis, in particular for non-small cell lung cancer (NSCLC) and liver hepatocellular carcinoma (LIHC). In addition, PAFAH1B3 expression was positively associated with tumor mutational burden (TMB), microsatellite instability (MSI), immune cell infiltration, immune-modulatory related gene expression, and diverse cancer drug sensitivity in human cancer. Increased PAFAH1B3 expression correlated with poor overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI) of NSCLC and LIHC, and has potential as an independent risk factor for overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI) during LIHC. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis confirmed that PAFAH1B3 is primarily involved in immune regulation. More importantly, results demonstrated that PAFAH1B3 was upregulated in liver cancer cells lines and that knockdown of this gene significantly inhibited cell proliferation, migration, and invasion in liver hepatocellular carcinoma (LIHC). In summary, this study elucidates the clinical significance and biological function of PAFAH1B3 during liver hepatocellular carcinoma (LIHC) and may serve as a potential biomarker for the diagnosis and prognosis of various cancer types.